POSSIBILITIES OF USING LOW-MOLECULAR-WEIGHT HEPARIN IN THE COMPLEX TREATMENT OF WOMEN WITH TUMORS OF THE REPRODUCTIVE SYSTEM - A. G. Kedrova; O. R. Shablovsky; S. A. Levakov; N. S. Vanke (Опухоли женской репродуктивной системы)
Benign and malignant tumors of the organs of the female reproductive system are the most common diseases requiring medical and surgical treatment. They are rarely the cause of acute complications. However, the thromboembolic disease is a serious illness, sometimes causing death due to acute the pulmonary embolism. Venous thromboembolism secondary to Benign and malignant tumors of the organs of the female reproductive system should be considered in a female presenting with abdominal mass and pelvic pressure. Thromboembolic disease secondary to large tumors should be treated with anticoagulation then hysterectomy. The article presents an analysis of modern literature on optimal prevention of the pulmonary thromboembolism in patients with tumors of the female reproductive system. There are analysis data of 17 (0.7 %) cases of the pulmonary thromboembolism that occurred of 2358 gynecological and oncogynecologic patients.